LEVEL OF KNOWLEDGE OF PHYSICAL EDUCATION PROFESSIONALS ABOUT AEROBIC AND RESISTANCE EXERCISE PRESCRIPTION FOR ELDERLY PEOPLE - Ceschini,Fábio (2018)
ABSTRACT Introduction: Regular aerobic and resistance exercises are recommended to improve functional capacity and quality of life in the elderly. Objective: To describe the familiarity of physical education professionals with the recommendation of aerobic and resistance exercise for the elderly, and to identify associated factors. Methods: We assessed 610 physical education professionals working in fitness academies in the city of São Paulo. Familiarity with the recommendation was assessed using a questionnaire constructed for this study. We assessed the criteria that make up the recommendation of aerobic and resistance exercise, following the American College of Sports Medicine guidelines. The data analysis with statistical significance of p <0.05 was carried out using the chi-square test and multiple logistic regression. Results: The level of knowledge of physical education professionals working in fitness centers, considering fulfilment of the criteria that make up the recommendation of aerobic and resistance exercise for the elderly, was limited, attaining only 9.3% and 12.6%, respectively. Age, number of jobs, completion of a graduate program and reading of scientific papers were factors associated with familiarity with the recommendation of resistance exercise. Factors associated with familiarity with aerobic exercise recommendation were: age, number of jobs and reading of scientific papers. Conclusion: The level of familiarity of physical education professionals with the recommendation of aerobic and resistance exercise for older people was low, suggesting the need for better professional training to meet the demand of older people at the fitness centers in the city of Sao Paulo. Level of Evidence I; Type of Study: Therapeutic Study - Investigation of Treatment Results.